Cloning and molecular characterization of toll-like receptor 4 (TLR-4) gene in Indian water buffalo - BHARDWAJ, RABIA; BRAH, G S; ARORA, J S; KAUR, SIMARJEET; MUKHOPADHYAY, C S (The Indian Journal of Animal Sciences, 2015)
TLR4 is one of the best characterized TLRs and is mainly activated by lipopolysaccharide (LPS), a component of gram-negative bacteria. It has been implicated in signal transduction events induced by LPS found in most gram-negative bacteria. The present study was carried out to clone, sequence and to in silico characterize TLR4 gene of Indian water buffalo (Bubalus bubalis). For this, primer-pair (viz. TLR4-2B, TLR4-3B and TLR4-5B) were designed from TLR4 gene complete cds sequences available on NCBI database. Peripheral blood sample was collected by direct puncturing of the jugular vein of apparently healthy Murrah buffalo and was processed to isolate peripheral blood mononuclear cells (PBMCs). Total RNA was extracted from PBMCs, cDNA was synthesized immediately and TLR4 cDNA was amplified. PCR amplification resulted in amplicons of 863bp, 871 bp and 899 bp, respectively. The amplified product was cloned in TA cloning vector. Recombinant clones were selected by blue-white screening on selective medium (LB agar containing X-gal, IPTG and ampicillin). Randomly 6 white colonies were picked and grown in LB broth containing ampicillin (100 μg/ml). Plasmids were isolated from clones following standard protocol and presence of insert was confirmed by PCR as well as restriction digestion by EcoRI. Positive clones were subjected to custom sequencing and the data obtained were analyzed. The deduced sequence was submitted to NCBI. Phylogenetic analysis indicated that the gene is conserved through evolution. The study suggested that TLR4 cds is highly conserved among the distant species under animal kingdom.